Functional and nutritional properties of rambutan (Nephelium lappaceum L.) seed and its industrial application: a review - Jahurul, M. H.A.; Azzatul, F. S.; Sharifudin, Md Shaarani; Norliza, M. J.; Mamat, Hasmadi; Lee, Jau Shya; Patricia, Matanjun; Jinap, Selamat; Ramlah George, M. R.; Khan, Mohammad Firoz; Sarker, Md. Zaidul Islam (Elsevier Ltd, 2020)
Background: Rambutan (Nephelium lappaceum L.) is an important commercial fruit in southeast Asia and is gaining more attention in recent years because it is juicy and sweet and has a refreshing flavour and an exotic appearance. It is commercialized for fresh consumption and is industrially processed as canned fruit, juices, jams, jellies, marmalades, and spreads. The seed is a major co-product of this industry and is worthy of attention for industrial applications and their feasibility.